2022
DOI: 10.3390/ijerph191710571
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Uterus Didelphys on Fertility and Pregnancy

Abstract: Uterus didelphys occurs as a result of abnormal fusion of the paramesonephric ducts and is characterized by complete duplication of uterine horns, cervix, and very often also the vagina or presence of longitudinal vaginal septum. Most women with a uterus didelphys are asymptomatic; some cases may coincide with dyspareunia or dysmenorrhea. The anomaly is associated with a higher risk of miscarriage, preterm labor, breech delivery, and decreased live births. We present the case of a 26-year-old woman (primigravi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…Genital neoplasms and endometriosis have been reported in a few cases (4). The rate of premature deliveries, abnormal fetal presentations, abortions, early rupture of the fetal membranes, cervical incompetence, postpartum haemorrhage, intrauterine growth restriction and cesarean deliveries are generally increased (14). According to Banu and colleagues, this anomaly has been reported in about 3.5 percent in sub fertile couples and about 13 percent in women with history of recurrent abortions (15).…”
Section: Discussionmentioning
confidence: 99%
“…Genital neoplasms and endometriosis have been reported in a few cases (4). The rate of premature deliveries, abnormal fetal presentations, abortions, early rupture of the fetal membranes, cervical incompetence, postpartum haemorrhage, intrauterine growth restriction and cesarean deliveries are generally increased (14). According to Banu and colleagues, this anomaly has been reported in about 3.5 percent in sub fertile couples and about 13 percent in women with history of recurrent abortions (15).…”
Section: Discussionmentioning
confidence: 99%
“…Pregnancy with uterus bicornis unicollis can cause various maternal and perinatal outcomes, including miscarriage (21%), prematurity (24%), ectopic pregnancy (2%), intrauterine growth restriction (11%), and an increased incidence of caesarean section (84%) [ 1 ]. The fertility of women with untreated uterus bicornis unicollis is better than women with other Müllerian duct disorders [ 6 ]. Risk factors for uterus bicornis unicollis include an increased risk of spontaneous abortion, fetal growth retardation, and prematurity [ 10 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study found that uterine didelphys does not necessitate a cesarean section, instead fetal presentation does [ 14 ]. In uterine didelphys, management of childbirth can be done either by vaginally or through cesarean section [ 6 , 25 ]. However, this condition is associated with fetal breech presentation and is the most common indication for cesarean delivery in women with uterine didelphys [ 1 , 4 , 13 , 21 , 26 ] Furthermore, if no coexistent symptom present, additional treatment to uterine disorder is deemed unnecessary [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent systematic review and meta-analysis showed that didelphys uterus was not associated with an increased incidence of infertility or miscarriage, but it was mainly associated with a higher risk of preterm delivery, preterm premature rupture of membranes, fetal malpresentation, cesarean, fetal growth restriction, and small for gestational age [ 3 ]. Regarding the higher risk of cesarean in this CUA, Cwiertnia et al demonstrated that the decision to perform cesarean depends on several factors, including fetal presentation, patient preference, and vaginal septum features [ 6 ].…”
Section: Discussionmentioning
confidence: 99%